Investigation of sediment samples from the Gulf of Trieste (northern Adriatic) by FTIR spectroscopy - Kovač, Nives (RMZ-materials and geoenvironment, 2005)
The infrared spectra (FTIR) of homogenised and HCI/HF treated surficial marinesediment samples from the Gulf of Trieste (northern Adriatic) were recorded to investigate the sediment composition. The samples were collected by gravity core sampler and analysed after freeze-drying and homogenisation. The results revealed carbonates and silicates as the major inorganic components, while the content of organic matter was rather low.
Keywords: Analysis; Carbonates; Geologic Sediments; Geološki sedimenti; Gulf of Trieste; Karbonati; Morska voda; Rentgenski žarki, lomljenje; Seawater; Silicates; Silikati; Spectrophotometry, Infrared; Spektrofotometrija infrardeča; Tržaški Zaliv; Voda, onesnaževalci kemični; Water Pollutants, Chemical; X-Ray Diffraction